2001
DOI: 10.1039/b008232p
|View full text |Cite
|
Sign up to set email alerts
|

2-tert-Butyl and 2-phenylphenylimido complexes of titanium(IV) and their olefin polymerisation activity

Abstract: Reaction of 7 equivalents of tert-butylamine with TiCl 4 in hexane at 0 ЊC gave [TiCl 2 (NCMe 3 )(NH 2 CMe 3 ) 2 ] 2 1 which on thermalisation with 2,6-diisopropylaniline in toluene gave [TiCl 2 (NC 6 H 3 Pr i 2 -2,6)(NH 2 CMe 3 ) 2 ] x 2. Imido exchange of [TiCl 2 (NCMe 3 )(NH 2 CMe 3 )] x with o-toluidine or 2-tert-butylaniline and addition of pyridine gave [TiCl 2 (NC 6 H 4 -Me-2)(py) 3 ] and [TiCl 2 (NC 6 H 4 CMe 3 -2)(py) 3 ] which crystallised to give [TiCl 2 (NC 6 H 4 Me-2)(py) 2 ] 2 3 and [TiCl 2 -(NC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…[30] Results and Discussion Synthesis and characterisation of cyclooctatetraenyl titanium imido complexes: Titanium imido dichloride starting materials [Ti(NR)Cl 2 (py) 3 ] (R= tBu, 2,6-Me 2 C 6 H 3 , 2,6-iPr 2 C 6 H 3 and 2-tBuC 6 H 4 ) were prepared according to previously described routes. [21,26] Reaction of these with either K 2 [COT] (COT = C 8 H 8 ) or the more sterically bulky Li 2 -[COT'']·1.8 THF (COT'' = 1,4-bis(trimethylsilyl)-1,3,5,7-cyclooctatetraenyl) gave products that depended critically on the exact nature of both the imido and cyclooctatetraenyl ring substituents. Addition of one equivalent of either K 2 [COT] or Li 2 [COT'']·1.8 THF to [Ti(NtBu)Cl 2 (py) 3 ] in THF at À50 8C gave a dark red solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[30] Results and Discussion Synthesis and characterisation of cyclooctatetraenyl titanium imido complexes: Titanium imido dichloride starting materials [Ti(NR)Cl 2 (py) 3 ] (R= tBu, 2,6-Me 2 C 6 H 3 , 2,6-iPr 2 C 6 H 3 and 2-tBuC 6 H 4 ) were prepared according to previously described routes. [21,26] Reaction of these with either K 2 [COT] (COT = C 8 H 8 ) or the more sterically bulky Li 2 -[COT'']·1.8 THF (COT'' = 1,4-bis(trimethylsilyl)-1,3,5,7-cyclooctatetraenyl) gave products that depended critically on the exact nature of both the imido and cyclooctatetraenyl ring substituents. Addition of one equivalent of either K 2 [COT] or Li 2 [COT'']·1.8 THF to [Ti(NtBu)Cl 2 (py) 3 ] in THF at À50 8C gave a dark red solution.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Both computational and experimental studies have been performed to probe the structure and reactivity of these systems. It has been shown that Group 4 transition-metal imides have potential in CÀH activation chemistry, [8][9][10][11][12][13][14][15][16] materials chemistry [17][18][19][20] and olefin polymerisation catalysis (with the imide acting as an "ancillary ligand"), [21][22][23] and that these systems can be utilised in an wide variety of stoichiometric and sometimes catalytic coupling reactions with unsaturated substrates. [6] Terminal titanium imido complexes were first structurally characterised in 1990, [24,25] and since then a large number of imido complexes with different ancillary ligands have been synthesised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogenisations were also attempted by using asc.wiley-vch.de modified polystyrene resins containing TMEDA groups. [58] However, preliminary results showed that these compounds were inactive [in contrast to the situation for the supported vanadium(V) catalysts of Gibson et al discussed below].…”
Section: Dedicated Cluster Reviewsmentioning
confidence: 81%
“…Some closely related work was reported by Nielson et al in which the triazacyclononane ligand is replaced by a TMEDA (tetramethylethylenediamine) ligand. [58] Since the TMEDA ligand only possesses two nitrogen donors the resulting compounds possess 14 valence electrons in contrast to the 16 valence electron complexes discussed above. In addition to the compound with a tert-butyl imido group (12), two further compounds were synthesised, each having arylimido groups with bulky ortho substituents.…”
Section: Dedicated Cluster Reviewsmentioning
confidence: 85%